Implications and Development Opportunities of the Container Library Program in Supporting Smart Society Development in Denpasar City - Ni Wayan Yuni Sugiastari; Nuning Indah Pratiwi (Journal of General Education and Humanities, 2026)
This study addresses the limited optimization of public literacy spaces in supporting the realization of a smart society in Denpasar. Although container libraries have been introduced as innovative public facilities, their strategic implications and development opportunities in strengthening smart society indicators remain underexplored. Therefore, this research aims to examine the implications and identify the development opportunities of the container library program in supporting smart society development in Denpasar City. The study focuses on two container libraries, namely Janger Library at Taman Janggan Renon and Widya Kumara Library at Lapangan I Gusti Ngurah Made Agung, as urban public literacy spaces. A qualitative descriptive approach was applied. Data were collected through observation, in-depth interviews, and documentation, with triangulation techniques employed to ensure data validity. Informants were purposively selected and consisted of 12 participants, including government officials, library managers and librarians, volunteers, and service users. The analytical framework integrates the principles of Reinventing Government, catalytic, community-owned, results-oriented, and customer-driven, with smart society indicators, namely community engagement, learning, security, and creativity. The findings reveal that the container library program significantly strengthens public literacy services by transforming urban public spaces into inclusive learning environments that foster community interaction, reading habits, and creative literacy activities. The program also supports the introduction of basic digital literacy and the provision of safe, child-friendly public spaces through cross-sector collaboration. Furthermore, substantial development opportunities exist in integrating digital literacy initiatives, expanding cross-sector partnerships, replicating container libraries in other urban parks, and promoting child-friendly literacy tourism. Overall, the program demonstrates strategic potential in advancing smart society development through the synergy of high-touch public engagement and high-tech digital services.